Concern in the Caribbean. - NORTON, Graham (1994)
Examines the growing increase in the Commonwealth Caribbean that the legitimate interests of the English-speaking democratic states are of little account to American policy-makers. Of direct concern are the consequences of NAFTA, while other areas include US views on CARICOM/Cuba relations, US intervention in Haiti, and US support for Latin banana producers.